Unique decision support system for cashew germplasm management - Mohana, G.S.; Nayak, M.G. (Journal of Plantation Crops, 2018)
ICAR-Directorate of Cashew Research, Puttur, Karnataka, the lead centre for conducting cashew research in India, conserves the highest number of cashew germplasm accessions in the country in its National Cashew Field Gene Bank. For the first time, a robust decision support system (DSS) has been developed with 478 accessions and 68 characters to manage and better utilise the germplasm resources. In the module, it is possible to select accessions based on multiple character combinations with information such as frequency distribution, images and pie diagrams. This is expected to help all the stakeholders involved in cashew research, production and processing for selection and subsequent utilisation of suitable germplasm accessions. The module can be accessed at https://cashew. icar.gov.in/dcr/.